Monitoring the impact of COVID-19 in Myanmar: Agricultural equipment retailers - July 2020 survey round - Takeshima, Hiroyuki; Win, Myat Thida; Masias, Ian (International Food Policy Research Institute, 2020)
Agricultural equipment retailers (ER) in Myanmar were originally interviewed by telephone in May 2020 and again in June 2020 to determine how their businesses were being affected by COVID-19 related restrictions. The results of those surveys were published in Myanmar Strategy Support Program Policy Notes 09 and 16, respectively. To trace the continuing impact of the COVID-19 pandemic on their economic activities, a third phone survey of ERs was done in July 2020. This Note reports on the results of this third survey, as well as changes in the businesses of agricultural equipment retailers since the first and the second surveys.